Enhancing Bawaslu’s investigative authority in electoral crime enforcement - Herman Balla; Wiwin Wiwin; Muh. Akbar Fhad Syahril; Phireri Phireri; Sunardi Purwanda; Yuspita Syawaliah (Privietlab, 2026)
This study examines the urgency of expanding the investigative authority over electoral crimes to the Election Supervisory Body or Badan Pengawas Pemilu (Bawaslu) in response to the persistent ineffectiveness of the Integrated Law Enforcement Center (Sentra Gakkumdu). This ineffectiveness is reflected in the high rate of case dismissals due to insufficient evidence and institutional discrepancies in legal interpretation, ultimately undermining the realization of electoral justice. This study adopts a normative (doctrinal) legal approach, employing statutory, conceptual, and case-based analyses. The data were analyzed qualitatively using descriptive, evaluative, and prescriptive methods. The findings demonstrate that expanding Bawaslu’s investigative authority is a philosophical, sociological, and juridical imperative. From a philosophical and sociological perspective, strengthening Bawaslu’s role is essential to ensure electoral justice and enhance public accountability, supported by the institution’s substantive expertise in electoral matters and a relatively high degree of public trust. Juridically, the Indonesian legal system provides a basis for granting investigative powers to Bawaslu’s Civil Servant Investigators or Penyidik Pegawai Negeri Sipil (PPNS) through an integrated law enforcement framework and the application of meritocratic principles, in line with existing practices in handling special criminal offences. This study recommends that such authority be explicitly regulated (expressis verbis) within electoral legislation through an omnibus law. Furthermore, it proposes a distribution of powers model in which the National Bawaslu is granted authority over national elections, while the Provincial and Regency/City Bawaslu oversee local elections under the coordination of the Indonesian National Police. This framework is expected to provide a legal policy solution for achieving a more effective and efficient system of electoral law enforcement in Indonesia.